Extreme sensory processing patterns and their relation with clinical conditions among individuals with major affective disorders. (28th February 2016) - Engel-Yeger, Batya; Muzio, Caterina; Rinosi, Giorgio; Solano, Paola; Geoffroy, Pierre Alexis; Pompili, Maurizio; Amore, Mario; Serafini, Gianluca
Abstract: Previous studies highlighted the involvement of sensory perception in emotional processes. However, the role of extreme sensory processing patterns expressed in hyper- or hyposensitivity was not thoroughly considered. The present study, in real life conditions, examined the unique sensory processing patterns of individuals with major affective disorders and their relationship with psychiatric symptomatology. The sample consisted of 105 participants with major affective conditions ranging in age from 20 to 84 years (mean=56.7±14.6). All participants completed the Temperament Evaluation of Memphis, Pisa, Paris and San Diego (TEMPS-A), the second version of the Beck Depression Inventory (BDI-II), and Adolescent/Adult Sensory Profile (AASP). Sensory sensitivity/avoiding hypersensitivity patterns and low registration (a hyposensitivity pattern) were prevalent among our sample as compared to normative data. About seventy percent of the sample showed lower seeking tendency. Stepwise regression analyses revealed that depression and anxious/cyclothymic affective temperaments were predicted by sensory sensory/avoiding. Anxious and irritable affective temperaments were predicted by low registration. Hyperthymic affective temperament and lower severity of depression were predicted by sensation seeking. Hyposensitivity or hypersensitivity may be "trait" markers of individuals with major affective disorders. Interventions should refer to the individual unique sensory profiles and their behavioral and functional impact in the context of real life. Highlights: Hyper/hypo sensitivity related to psychiatric symptomatology were not investigated. Low registration may enhance the severity of some psychiatric conditions. Sensation seeking may presumably serve as a protective pattern. Interventions may be targeted according to the subjects' unique sensory profiles.